The Role of Monthly Economic Statistical Bulletins - Dziobek, Claudia (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2002)
Monthly economic statistical bulletins issued by central banks and national statistical offices, the focus of this study, are well established in countries with advanced statistical systems. Such bulletins present a synopsis of current economic trends and cater to a broad group of users involved in policy, markets, media, and research. Compendium bulletins serve as a reference point, contribute to public economic knowledge and transparency, and can add to international visibility. The authors find that only about half of developing countries produce monthly bulletins. Based on experience in industrial countries and a survey of 22 successful bulletins from developing countries, this paper highlights the role of such bulletins and discusses selected aspects of their content, production, and dissemination.